Advances in communication control networks - Tarbouriech, Sophie (Lecture Notes in Control and Information Sciences, 2005)
The area of communication and computer networks has become a very active field of research by the control systems community in the last years. Tools from convex optimization and control theory are playing increasing roles in efficient network utilization, fair resource allocation, and communication delay accommodation and the field of Networked Control systems is fast becoming a mainstay of control systems research and applications. This carefully edited book brings together solicited contributions from experts in the various areas of communication/control networks referring to both networks under control (control in networks) as well as networked control systems (control over networks). The aim of this book is to reverse the trend of fragmentation and specialization in Communication Control Networks connecting various interdisciplinary research fields including control, communication, applied mathematics and computer science. Stochastic fluid models for the on-line control of communication networks -- Stability analysis of window flow control -- H-infinity and LMMSE based capacity predictors for flow -- Control in communication networks -- Models and methods for analyzing congestion control and active management schemes -- Delay effects on the stability of various fluid models encountered in high-speed networks -- Decentralized track engineering in the internet: a sliding mode approach -- Modeling the internet congestion control using the smith predictor and input shaping -- Saturated controller design of an ABR explicit rate algorithm for ATM switches -- State-space models for control and identification -- Global stability of nonlinear congestion control with time-delay -- On the optimization of load balancing in distributed networks in the presence of delay -- Bounds on achievable performance of load balancing algorithms for parallel computations -- On position tracking in bilateral teleoperation -- Suboptimal control techniques for hybrid systems operating via networks -- Communication requirements for networked control -- A new approach to fault diagnosis, with an application to demodulation.